the INTELLECTUAL EDUCATION AND CHARACTER BUILDING IN THE FACE OF THE TIMES: The INTELLECTUAL EDUCATION AND CHARACTER BUILDING IN THE FACE OF THE TIMES - Rusgowanto, Fransisca; Febrian, Juan; Jocellin, Aloysia (Jurnal Abdi Masyarakat Nusantara, 2023)
: Community Service is one of the duties of the Tridharma of Higher Education. This activity is carried out in the form of a webinar. Character education aims to improve the quality of implementation and results of education in schools that lead to the achievement of the formation of character and noble morals of students as a whole, integrated and balanced according to graduate competency standards. Through character education it is hoped that students will be able to independently improve and use their knowledge, study and internalize and personalize character values and noble morals so that they are manifested in everyday behavior. It is the spearhead of intellectual education which needs to be balanced with character education. This webinar is designed according to the vision and mission for parents of students at SMPK Sang Timur, Tomang, Jakarta in implementing character education so that it can lead them to become more mature in processing emotions and become more confident so that they are not easily influenced to become perpetrators of drug abuse, and can increase students' abilities in developing their potential so that they are more able to explore and be creative in positive and useful things.